International standards for symphysis-fundal height based on serial measurements from the Fetal Growth Longitudinal Study of the INTERGROWTH-21st Project: prospective cohort study in eight countries. (7th November 2016) - Papageorghiou, Aris T; Ohuma, Eric O; Gravett, Michael G; Hirst, Jane; da Silveira, Mariangela F; Lambert, Ann; Carvalho, Maria; Jaffer, Yasmin A; Altman, Douglas G; Noble, Julia A; Bertino, Enrico; Purwar, Manorama; et al.
Abstract : Objective  To create international symphysis-fundal height standards derived from pregnancies of healthy women with good maternal and perinatal outcomes. Design  Prospective longitudinal observational study. Setting  Eight geographically diverse urban regions in Brazil, China, India, Italy, Kenya, Oman, United Kingdom, and United States. Participants  Healthy, well nourished pregnant women enrolled into the Fetal Growth Longitudinal Study component of the INTERGROWTH-21 st Project at 9-14 weeks' gestation, and followed up until birth. Main outcome measures  Symphysis-fundal height was measured every five weeks from 14 weeks' gestation until birth using standardised methods and dedicated research staff who were blinded to the symphysis-fundal height measurements by turning the tape measure so that numbers were not visible during examination. The best fitting curve was selected using second degree fractional polynomials and further modelled in a multilevel framework to account for the longitudinal design of the study. Results  Of 13 108 women screened in the first trimester, 4607 (35.1%) met the study entry criteria. Of the eligible women, 4321 (93.8%) had pregnancies without major complications and delivered live singletons without congenital malformations. The median number of symphysis-fundal height measurements was 5.0 (range 1-7); 3976 (92.0%) women had four or more measurements. Symphysis-fundal height measurements increased almost linearly with gestational age; data were used to determine fitted 3rd, 50th, and 97th centile curves, which showed excellent agreement with observed values. Conclusions  This study presents international standards to measure symphysis-fundal height as a first level screening tool for fetal growth disturbances.